Support for Aboriginal health services in reducing harms from alcohol: 2‐year service provision outcomes in a cluster randomized trial. (20th October 2021) - Dzidowska, Monika; Lee, K. S. Kylie; Conigrave, James H.; Dobbins, Timothy A.; Hummerston, Beth; Wilson, Scott; Haber, Paul S.; Gray, Dennis; Conigrave, Katherine M.
Abstract: Background and aims: There is a higher prevalence of unhealthy alcohol use among Indigenous populations, but there have been few studies of the effectiveness of screening and treatment in primary health care. Over 24 months, we tested whether a model of service‐wide support could increase screening and any alcohol treatment. Design: Cluster‐randomized trial with 24‐month implementation (12 months active, 12 months maintenance). Setting: Australian Aboriginal Community Controlled primary care services. Participants: Twenty‐two services (83 032 clients) that use Communicare practice software and see at least 1000 clients annually, randomized to the treatment arm or control arm. Intervention and comparator: Multi‐faceted early support model versus a comparator of waiting‐list control (11 services). Measurements: A record (presence = 1, absence = 0) of: (i) Alcohol Use Disorders Identification Test—Consumption (AUDIT‐C) screening (primary outcome), (ii) any‐treatment and (iii) brief intervention. We received routinely collected practice data bimonthly over 3 years (1‐year baseline, 1‐year implementation, 1‐year maintenance). Multi‐level logistic modelling was used to compare the odds of each outcome before and after implementation. Findings: The odds of being screened within any 2‐month reference period increased in both arms post‐implementation, but the increase was nearly eight times greater in early‐support services [odds ratio (OR) = 7.95, 95% confidence interval (CI) = 4.04–15.63, P  < 0.001]. The change in odds of any treatment in early support was nearly double that of waiting‐list controls (OR = 1.89, 95% CI = 1.19–2.98, P  = 0.01) but was largely driven by decrease in controls. There was no clear evidence of difference between groups in the change in the odds of provision of brief intervention (OR = 1.95, 95% CI = 0.53–7.17, P  = 0.32). Conclusions: An early support model designed to aid routine implementation of alcohol screening and treatment in Aboriginal health services resulted in improvement of Alcohol Use Disorders Identification Test—Consumption screening rates over 24 months of implementation, but the effect on treatment was less clear.